Ujaran Kebencian dalam Kolom Komentar Media Berita Online BABE - Salvatore, Anggie Ray; Suparwa, I Nyoman; Sri Satyawati, Made (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p13, 2022)
Hate speech is a language phenomenon that often appears on social media nowadays. This was exacerbated by the political intensity between supporting and opposing groups of the government. The commentary column which contains news on the topic of government is one of the ways to spread hate speeches. Therefore, this study aims to analyze the hate speech that appears in the commentary column of an online news media called BABE with the aim of finding the form of lingual markers, the speech act meaning, and the speech act function of the hate speech. The results of this study found that lingual markers in hate speech were divided into three categories, namely words, phrases and utterances. The meaning of hate speech is illocutionary and is classified into seven types of hate speech, including insult, defamation, desecration, unpleasant action, provocation, incitement, and hoax. Meanwhile, the speech act function that appears in hate speech has four speech act functions, namely the assertive function, the directive function, the commissive function, and the expressive function.